2017
DOI: 10.1097/qad.0000000000001637
|View full text |Cite
|
Sign up to set email alerts
|

Pathways from sexual stigma to incident HIV and sexually transmitted infections among Nigerian MSM

Abstract: Objectives Sexual stigma affecting men who have sex with men (MSM) in Nigeria may be an important driver of HIV and other sexually transmitted infections (STIs), but potential mechanisms through which this occurs are not well understood. This study assessed the contributions of suicidal ideation and sexual risk behaviors to causal pathways between stigma and HIV/STIs. Design Data were collected from the TRUST/RV368 Study, a prospective cohort of 1,480 MSM from Abuja and Lagos, Nigeria. Methods Participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 37 publications
2
35
0
Order By: Relevance
“…The relationship between HIV and uniformed officers refusal to provide protection varies by legal status (MH p value < 0.01) with an increased odds in settings without legal specification (aOR: 1.64; 95% CI: 1.29-2.08; p value < 0.001) and criminalized settings (aOR: 1.38; 95% CI: 1.10-1.72; p value = 0.005) compared with partially legalized settings. Blackmail is associated with HIV in non-specified settings (aOR: 1.50; 95% CI: 1.37-1.65; p value: < 0.001) and criminalized settings (aOR: 1.35; 95% CI: 1.07-1.71; p value: 0.010) compared with partially legalized 27 (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) Median years in sex work (IQR) settings. HIV is associated with physical violence in criminalized settings versus partially legalized settings (aOR: 1.34; 95% CI: 1.11-1.62; p value = 0.002).…”
Section: Study Sample Characteristics a Total Of 7259 Female Sex Wormentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between HIV and uniformed officers refusal to provide protection varies by legal status (MH p value < 0.01) with an increased odds in settings without legal specification (aOR: 1.64; 95% CI: 1.29-2.08; p value < 0.001) and criminalized settings (aOR: 1.38; 95% CI: 1.10-1.72; p value = 0.005) compared with partially legalized settings. Blackmail is associated with HIV in non-specified settings (aOR: 1.50; 95% CI: 1.37-1.65; p value: < 0.001) and criminalized settings (aOR: 1.35; 95% CI: 1.07-1.71; p value: 0.010) compared with partially legalized 27 (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) Median years in sex work (IQR) settings. HIV is associated with physical violence in criminalized settings versus partially legalized settings (aOR: 1.34; 95% CI: 1.11-1.62; p value = 0.002).…”
Section: Study Sample Characteristics a Total Of 7259 Female Sex Wormentioning
confidence: 99%
“…Understanding sex work-related stigmas, especially across different legal contexts has direct implications for the implementation and effectiveness of HIV treatment programs. Where assessed, perceived, anticipated, and enacted stigmas consistently challenge progress along the HIV treatment cascade by limiting engagement in prevention, care, and treatment services [27][28][29][30] . Moreover, intersecting stigmas have been associated with prevalent HIV infection and limited uptake of services along the HIV treatment cascade across sub-Saharan Africa [31][32][33] .…”
mentioning
confidence: 99%
“…39,40 The study also identified a substantial need for diagnosis and management of other sexually transmitted infections, and new prevention interventions. [40][41][42][43][44][45][46][47] Study findings have subsequently been incorporated directly into prevention and clinical service approaches at the community centers.…”
Section: Rv516mentioning
confidence: 99%
“…Globally, men who have sex with men (MSM) and transgender women (TGW) bear a disproportionate burden of HIV as compared to the general population [1][2][3]. In Nigeria, like many other parts of the world where same-sex sexual practices are criminalized, issues of discrimination, stigma, and fear create barriers to care and impede implementation of HIV preventive strategies [4][5][6][7][8][9], contributing to a disproportionate burden of HIV and other sexually transmitted infections [10][11][12]. The 2017 UNAIDS Databook noted an HIV prevalence of 23% among MSM in Nigeria and we have previously reported HIV prevalence as high as 66% among MSM and TGW in Lagos [13,14].…”
Section: Introductionmentioning
confidence: 99%